Serum paraoxonase activity and oxidative stress levels in patients with cutaneous anthrax. (July 2017) - Karadas, S; Aslan, M; Ceylan, MR; Sunnetcioglu, M; Bozan, N; Kara, H; Demir, H
Introduction: Anthrax is a bacterial disease caused by the aerobic sporeforming bacterium Bacillus anthracis . It has been suggested that oxidative stress plays an important role in the pathogenesis of B. anthracis . The aim of this study was to investigate serum paraoxonase 1 (PON1) activity, catalase activity, malondialdehyde (MDA) levels, and superoxide dismutase (SOD) levels in patients with cutaneous anthrax. Materials and methods: Fifteen patients with cutaneous anthrax and 15 healthy controls were enrolled in this study. The serum MDA levels, SOD levels, paraoxonase, arylesterase, and catalase activities were measured using a spectrophotometer. Results: The serum SOD levels, paraoxonase, arylesterase, and catalase activities were significantly lower in patients with cutaneous anthrax than in controls (for all, p < 0.001), whereas MDA levels were significantly higher ( p < 0.001). No significant correlation was found between serum paraoxonase activity, arylesterase activity, SOD levels, and MDA levels (all, p > 0.05) in patients with cutaneous anthrax. Conclusions: The current study was the first to show decreased antioxidant levels and increased oxidant levels in patients with cutaneous anthrax. Therefore, decreased PON1 activity may play a role in the pathogenesis of cutaneous anthrax.